Comprehensive characterization of the competitive endogenous RNA network revealing its immune-related functions in hepatic ischemia-reperfusion injury - LiRong Liu; Qi Wang; Shuang Qin; Chang Su; Xin Hai; Zhenkuan Yuan (PLoS ONE, 2025)
Hepatic ischemia-reperfusion injury (HIRI) is a common complication in liver surgery and transplantation. Recent studies have revealed the significant role of the competing endogenous RNA (ceRNA) network in HIRI. Herein, we comprehensively analyzed the HIRI-related ceRNA network and its correlation with immune-related pathways and immune cells in HIRI patients. We identified 449 lncRNAs, 26 miRNAs, and 548 mRNAs differentially expressed in HIRI patients. We constructed a HIRI-related ceRNA network in liver transplant patients consisting of 3 lncRNAs, 3 miRNAs, and 29 mRNAs. Biological function analysis showed that the HIRI-related ceRNA network contributes to HIRI progression by regulating calcium ion-related regulatory pathways and processes. An immune-related ceRNA subnetwork, which consists of 1 lncRNA (PARD6G-AS1), 1 miRNA (hsa-miRNA-125b-5p), and 4 mRNAs (PLAU, CCR5, FGF5 and IL24) was obtained. The immune-related ceRNA subnetwork was significantly related to the immune-related pathways and immune cell infiltration. The PARD6G-AS1/miR-125b-5p/IL24 axis was identified as a potential ceRNA sponge that may influence NK cell activity in HIRI. Our results underlined that the lncRNA-miRNA-mRNA ceRNA network can positively or negatively regulate immune-related functions and infiltrating immune cells mediated HIRI, which could provide further insight into novel molecular therapeutic targets.